Exploring the impact of an economic‐centric approach to evaluating cultural activities: Evidence from a regional music festival. Issue 3 (6th March 2021) - Safari, Dominik; Glow, Hilary; Noblet, Andrew; Pyman, Amanda
Abstract: Despite the numerous benefits associated with state‐funded festivals, little is known about how New Public Management ideals (e.g. emphasis on economic returns, short‐term funding cycles) influence the extent to which these events can create value across social, cultural, and economic dimensions. Drawing on recent theoretical advancements around ecology of culture, we used a single‐case study design that included an embedded sub‐case to examine how value is assessed in an Australian‐based regional music festival and the implications for generating economic (e.g. ticket sales), social (e.g. sense of belonging), and cultural value (e.g. revitalising local traditions). The findings suggest that although prioritising economic value ahead of social and cultural outcomes can ultimately prove counterproductive, the experiences of those involved in the sub‐case indicate that a more holistic approach to festival self‐assessment can strengthen social, cultural, and economic outcomes and enhance the functioning of the sub‐case. These findings have important theoretical and practical implications, particularly in terms of reinforcing key elements of the ecosystem framework and helping to identify the ways in which festival ecosystems can be supported to enhance value creation. Abstract : Despite the numerous benefits associated with festivals, little is known about how New Public Management ideals influence the extent to which they can create value across social, cultural, and economic dimensions. Drawing on ecology of culture frameworks, this study examines how value is assessed in an Australian regional music festival.